Carbon nanotube / porous carbon composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611509277.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]然而,现有CNTs/多孔碳复合材料的制备仍存在明显不足:常用纯化学试剂、生物质或精制碳源作为前驱体,原料成本较高;多孔碳制备与CNTs生长多分步进行方式,流程冗长,操作繁琐,不利于规模化生产
本发明以褐煤为碳前驱体,其富含含氧官能团、结构疏松,且含有Fe、Ni等多种金属元素,在高温条件下可作为天然催化活性中心,促进碳纳米管的生成。本发明通过K2CO3活化结合高温碳化策略,利用褐煤中固有金属组分的催化作用,引导碳源发生重构,形成具有一定石墨化程度的碳纳米结构,实现碳纳米管(CNTs)的原位生长,进而在碳基体内部构建连续导电网络,同步实现孔结构与导电通道的协同调控。
Smart Images

Figure CN123017746A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon-based energy storage materials technology, and in particular to a carbon nanotube / porous carbon composite material, its preparation method, and its application. Background Technology
[0002] Supercapacitors, as a novel electrochemical energy storage device, have shown broad application prospects in renewable energy storage, portable electronic devices, and electric vehicles due to their advantages such as high power density, wide operating temperature range, long cycle life, and environmental friendliness. Electrode materials are one of the key factors determining the performance of supercapacitors, and carbon-based materials, with their advantages of high specific surface area, excellent conductivity, good chemical stability, and sustainable sourcing, have become a research hotspot for supercapacitor electrode materials.
[0003] Constructing efficient conductive networks within porous carbon materials is a crucial strategy for enhancing the electrochemical performance of electrode materials. Carbon nanotubes (CNTs) possess excellent conductivity and can be used to construct three-dimensional conductive networks; porous carbon, on the other hand, provides a high specific surface area and abundant ion storage sites. Combining CNTs with porous carbon holds promise for achieving a complementary advantage in conductivity and specific surface area, leading to high-performance supercapacitor electrode materials.
[0004] However, existing methods for preparing CNTs / porous carbon composites still have significant shortcomings: they commonly use pure chemical reagents, biomass, or refined carbon sources as precursors, resulting in high raw material costs; the preparation of porous carbon and the growth of CNTs are often carried out in multiple steps, leading to lengthy and cumbersome processes that are not conducive to large-scale production. Furthermore, in composites prepared by existing methods, the interaction between CNTs and the carbon matrix is mostly a simple physical mixture with weak interfacial bonding, making it difficult to form a stable, integrated conductive network, thus limiting charge transport efficiency and the overall performance of the electrode material. Summary of the Invention
[0005] The purpose of this invention is to provide a carbon nanotube / porous carbon composite material, its preparation method, and its application. The carbon nanotube / porous carbon composite material prepared by the method of this invention has high specific capacitance, excellent rate performance, and good cycling stability.
[0006] To achieve the above objectives, the present invention provides a method for preparing carbon nanotube / porous carbon composite materials, comprising the following steps: Lignite powder was mixed with K2CO3 and ground to obtain a premixed precursor. The premixed precursor was carbonized and acid-washed under an inert atmosphere to obtain a carbon nanotube / porous carbon composite material.
[0007] In this invention, the method for preparing the lignite powder preferably includes the following steps: grinding and sieving lignite to obtain lignite powder; the lignite is preferably low-rank lignite, specifically lignite from eastern Inner Mongolia; this invention does not have any special limitation on the grinding and sieving method, and any method known to those skilled in the art can be used.
[0008] In this invention, the particle size of the lignite powder is preferably ≤200 mesh; the mass ratio of the lignite powder to K2CO3 is preferably 1:0.75~2, specifically 1:1 or 1:1.5; the grinding method is preferably ball milling; the ball milling time is preferably 1~3 hours, specifically 2 hours.
[0009] In this invention, the inert atmosphere is preferably nitrogen and / or argon, specifically nitrogen; the carbonization preferably includes a first-stage carbonization and a second-stage carbonization performed sequentially; the temperature of the first-stage carbonization is preferably 400~600℃, specifically 500℃; the holding time of the first-stage carbonization is preferably 1~3h, specifically 2h; the heating rate to the first-stage carbonization temperature is 2~4℃ / min, specifically 3℃ / min; the temperature of the second-stage carbonization is 800~1000℃, specifically 900℃; the holding time of the second-stage carbonization is preferably 1~3h, specifically 2h; the heating rate to the second-stage carbonization temperature is 2~4℃ / min, specifically 3℃ / min.
[0010] In this invention, the pickling preferably involves sequential washing with hydrofluoric acid, hydrochloric acid, and water; the mass fraction of the hydrofluoric acid is preferably 15%~25%, specifically 20%; the washing time with hydrofluoric acid is preferably 1~3 hours, specifically 2 hours; the washing method with hydrofluoric acid is preferably ultrasonic washing, and this invention does not have special requirements for ultrasonic washing, and washing methods well known to those skilled in the art can be used; the concentration of the hydrochloric acid is preferably 0.5~1.5 mol / L, specifically 1 mol / L; the washing time with hydrochloric acid is preferably 1~3 hours, specifically 2 hours; the washing method with hydrochloric acid is preferably ultrasonic washing, and this invention does not have special requirements for ultrasonic washing, and washing methods well known to those skilled in the art can be used; the water washing is preferably performed until the pH of the washing solution is neutral.
[0011] In this invention, the pickling process preferably includes drying; the drying temperature is preferably 70~90℃, specifically 80℃; and the drying time is preferably 6~10h, specifically 8h.
[0012] The present invention provides a carbon nanotube / porous carbon composite material prepared by the above preparation method.
[0013] This invention also provides the application of the above-mentioned carbon nanotube / porous carbon composite material in the preparation of supercapacitor electrodes.
[0014] The present invention also provides a supercapacitor electrode, the supercapacitor electrode comprising the above-mentioned carbon nanotube / porous carbon composite material and PVDF.
[0015] In this invention, the supercapacitor electrode further includes conductive carbon black; the mass content of the conductive carbon black in the supercapacitor is 0%~10%.
[0016] The present invention has the following beneficial effects: This invention uses lignite as a carbon precursor, which is rich in oxygen-containing functional groups, has a loose structure, and contains various metal elements such as Fe and Ni. Under high-temperature conditions, it can serve as a natural catalytic active center, promoting the formation of carbon nanotubes. This invention utilizes a K₂CO₃ activation combined with a high-temperature carbonization strategy, leveraging the catalytic effect of the inherent metal components in lignite to guide the reconstruction of the carbon source, forming a carbon nanostructure with a certain degree of graphitization. This achieves in-situ growth of carbon nanotubes (CNTs), thereby constructing a continuous conductive network within the carbon matrix and simultaneously realizing the synergistic regulation of pore structure and conductive channels.
[0017] This invention achieves simultaneous chemical activation and pore-forming of the carbon skeleton by K2CO3 and in-situ growth of CNTs catalyzed by inherent metal components in lignite through the carbonization process; it eliminates the need for stepwise porous carbon preparation and CNT growth, resulting in a simplified process flow suitable for large-scale production.
[0018] This invention employs a segmented carbonization process. In the first stage of carbonization, volatile components (hydrocarbon gases, hydrogen, sulfur-containing gases, and nitrogen-containing gases) in lignite are released in an orderly manner and undergo preliminary carbonization, forming a stable carbon skeleton. This effectively avoids pore collapse and structural breakage caused by concentrated gas escape due to rapid heating. In the second stage of carbonization, the chemical activation of the carbon skeleton by K2CO3 to create pores and the in-situ growth of carbon nanotubes (CNTs) catalyzed by the inherent Fe components in lignite through CO disproportionation are simultaneously and synergistically achieved. This allows CNTs to grow uniformly on the surface and inside the pores of the porous carbon matrix, forming an integrated conductive network tightly bound to the carbon skeleton, rather than through traditional physical mixing. This significantly reduces interfacial contact resistance. The segmented carbonization process of this invention can effectively control the graphitization degree and defect level of the carbon skeleton and avoid pore wall collapse and CNT agglomeration caused by excessive etching. This allows the material to maintain a high specific surface area and reasonable pore size distribution while possessing excellent conductivity and structural stability.
[0019] In this invention, the in-situ constructed conductive network of CNTs endows the composite material with excellent intrinsic conductivity. When preparing the supercapacitor electrode, no additional conductive carbon black is needed (or only a small amount is required), avoiding the problem of excessive conductive carbon black occupying active sites and increasing contact resistance in traditional electrodes. This allows for full utilization of the material's specific surface area and pore structure, significantly improving the effective utilization rate of the active material (carbon nanotube / porous carbon composite material), thereby enhancing the overall energy storage performance of the electrode. Example data show that, when used as a supercapacitor electrode material without the addition of conductive carbon black, 0.5 A·g -1 The specific capacitance can reach 500 F·g at current density. -1 In a system with a small amount of conductive carbon black, 0.5 A·g -1 The specific capacitance reaches 340 F·g -1 Furthermore, after 8000 cycles, the capacitance retention rate can reach 87%, combining high specific capacitance, excellent rate performance, and good cycle stability. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 This is a schematic diagram of the preparation process of carbon nanotube / porous carbon composite material in Example 1; Figure 2 SEM images of the materials prepared in Examples 1-4 and Comparative Examples 1-5; Figure 2 In the image, 'a' represents the SEM image of KCM-0. Figure 2 In the image, b represents the SEM image with KCM-0.25. Figure 2 In the image, c represents the SEM image of KCM-0.5; Figure 2 In the image, d represents the SEM image with KCM-0.75. Figure 2 In this context, 'e' represents the SEM image of KCM-1. Figure 2 f in the image is a SEM image of KCM-1.5; Figure 2 In the image, g represents the SEM image of KCM-2; Figure 2 In the image, h represents the SEM image of KCM-3; Figure 2 In this context, i represents the SEM image of KCM-4; Figure 3 SEM and elemental mapping of KCM-1.5 obtained in Example 2; Figure 3 In the image, 'a' represents the SEM image of KCM-1.5. Figure 3 In this context, 'b' represents the C element mapping diagram. Figure 3 In this context, 'c' represents the O-element mapping diagram. Figure 3 In this context, d represents the Fe element mapping diagram. Figure 3 In this context, 'e' represents the K-element mapping graph. Figure 3 f in the figure represents the Si element mapping diagram; Figure 4 The specific heat capacity of different electrodes with added conductive graphite at different current densities; Figure 5 The specific heat capacity values of different electrodes without conductive graphite at different current densities; Figure 6 The graphs show the cycle stability and coulombic efficiency of different electrodes. Figure 6 In the figure, 'a' represents the cycle stability and coulombic efficiency curves of the electrode (without conductive carbon black) made with KCM-1.5 as the active material. Figure 6 In the figure, b represents the cycle stability and coulombic efficiency curves of the electrode made with KCM-0.75 as the active material (with added conductive carbon black). Detailed Implementation
[0022] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0023] The lignite used in this embodiment of the invention is lignite from eastern Inner Mongolia, and the polyvinylidene fluoride (PVDF) used is (analytical grade, Shanghai Aladdin Reagent Co., Ltd.).
[0024] Example 1 After grinding the lump lignite, it was subjected to standard sieving to obtain lignite powder with a particle size of less than 200 mesh; Lignite powder and K2CO3 were mixed at a mass ratio of 1:0.75 and ball-milled for 2 hours to obtain a premixed precursor. The premixed precursor was placed in a tube furnace and heated to 500℃ at a rate of 3℃ / min under N2 atmosphere, and held for 1 h; then heated to 900℃ at the same rate and held for 2 h; after naturally cooling to room temperature, it was ultrasonically washed in 20% hydrofluoric acid for 2 h, and then transferred to 1 mol / L hydrochloric acid for ultrasonic washing for 2 h; then washed repeatedly with water until the washing solution reached neutral pH; and finally vacuum dried at 80℃ for 8 h to obtain carbon nanotube / porous carbon composite material, denoted as KCM-0.75.
[0025] The schematic diagram of the preparation process of the carbon nanotube / porous carbon composite material in this embodiment is shown below. Figure 1 As shown.
[0026] Example 2 The preparation method of this embodiment is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:1.5, and carbon nanotube / porous carbon composite material is obtained, denoted as KCM-1.5.
[0027] Example 3 The preparation method of this embodiment is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:1, and carbon nanotube / porous carbon composite material is obtained, which is denoted as KCM-1.
[0028] Example 4 The preparation method of this embodiment is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:2, and carbon nanotube / porous carbon composite material is obtained, which is denoted as KCM-2.
[0029] Comparative Example 1 The preparation method of this comparative example is basically the same as that of Example 1, except that K2CO3 is not added, and a porous carbon composite material is obtained, which is denoted as KCM-0.
[0030] Comparative Example 2 The preparation method of this comparative example is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:0.25, and carbon nanotube / porous carbon composite material is obtained, denoted as KCM-0.25.
[0031] Comparative Example 3 The preparation method of this comparative example is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:0.5, and carbon nanotube / porous carbon composite material is obtained, denoted as KCM-0.5.
[0032] Comparative Example 4 The preparation method of this comparative example is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:3, and carbon nanotube / porous carbon composite material is obtained, which is denoted as KCM-3.
[0033] Comparative Example 5 The preparation method of this comparative example is basically the same as that of Example 1, except that the mass ratio of lignite powder to K2CO3 is 1:4, and carbon nanotube / porous carbon composite material is obtained, which is denoted as KCM-4.
[0034] The materials obtained in Examples 1-4 and Comparative Examples 1-5 were characterized by SEM, and the results are as follows: Figure 2 As shown. By Figure 2 As can be seen, in Comparative Example 1 without the addition of activator K2CO3, the sample mainly exhibits a dense blocky structure with a relatively smooth surface. Almost no obvious pores or CNT formation were observed, indicating that the carbonization process at this stage primarily focused on framework preservation, resulting in a relatively closed structure. With the K2CO3 ratio increasing to 0.25-0.5, the carbon matrix gradually underwent etching, surface roughening, and the emergence of preliminary porous structures. Simultaneously, a small number of short and dispersed CNTs were observed, indicating that the activator began to promote carbon structure reconstruction and facilitated the exposure of catalytic sites and the initial growth of CNTs. When the activator ratio was further increased to 0.75-2, the microstructure of the material was significantly optimized. A large number of CNTs grew uniformly on the carbon matrix surface and within the pores, exhibiting an interwoven network structure, which is beneficial for constructing continuous conductive pathways. Simultaneously, the carbon framework formed a rich and interconnected porous structure under activation, with thinner pore walls and a significantly increased surface roughness, exhibiting typical chemical activation characteristics. Among the samples, when the K₂CO₃ ratio was 2, the CNTs distribution was the most uniform, and the pore structure maintained good integrity and connectivity without significant collapse or blockage, indicating that CNT growth and pore structure construction reached a relatively optimal synergistic state at this point. When the K₂CO₃ ratio continued to increase to 3-4, the material structure began to deteriorate. Although the CNT length increased, the carbon matrix underwent excessive etching, manifested as pore wall collapse, structural fragmentation, and localized agglomeration. Simultaneously, some CNTs exhibited entanglement, leading to pore channel obstruction. This indicates that excessively high activator dosage can disrupt the stability of the carbon framework and weaken the synergistic effect between the porous structure and the conductive network.
[0035] The KCM-1.5 prepared in Example 2 was characterized by SEM and elemental mapping, and the results are as follows: Figure 3 As shown. By Figure 3It is evident that KCM-1.5 is primarily composed of stacked sheet-like carbon structures with a distinct surface undulation, exhibiting a relatively loose three-dimensional framework. Numerous slender carbon nanotubes (CNTs) can be observed on the carbon matrix surface and in its interstices. These CNTs are relatively uniformly distributed, some exhibiting an interwoven state, forming a continuous network structure in localized areas. This structure facilitates the establishment of stable conductive pathways within the material while retaining a certain amount of porosity, providing channels for electrolyte ion transport. Elemental distribution results further indicate that C is uniformly distributed throughout the region, signifying a continuous and intact carbon framework; O is also relatively uniformly distributed, indicating that the material surface still contains a certain amount of oxygen-containing groups, which is related to the raw materials themselves and surface defects generated during activation. Fe exists in a dispersed dotted form, indicating a relatively uniform distribution of the catalytic metal in the matrix, providing the necessary conditions for carbon nanotube formation. K content is low, and no obvious enrichment areas are observed, indicating that most of the activator has been removed during the reaction and post-treatment processes. Si is distributed in small amounts as dots, mainly originating from mineral impurities in the raw materials. Combining morphology and elemental distribution, it can be seen that the etching degree of the KCM-1.5 carbon framework is well matched with the growth of CNTs: on the one hand, a relatively interconnected porous structure is formed; on the other hand, CNTs can grow uniformly on the substrate surface and form a certain degree of network structure. No obvious collapse or severe aggregation was observed in the overall structure, indicating that KCM-1.5 has achieved a relatively coordinated structural state, which is beneficial to improving the electrochemical performance of supercapacitors.
[0036] Test Example 1 The materials obtained in Examples 1-4 and Comparative Examples 1-5 were mixed with conductive carbon black and 2% PVDF solution at a mass ratio of 8:1:1, respectively. N-methylpyrrolidone was added as a solvent, and the mixture was stirred on a magnetic stirrer for 8 hours to obtain a slurry. This slurry was then coated onto a 1×1.5 cm carbon cloth, and the coated sample was placed in a vacuum drying oven at 80°C for 12 hours to obtain a supercapacitor electrode sheet. The loading of the supercapacitor electrode sheets in this test example was 1.6 mg, and the mass of the materials obtained in Examples 1-4 and Comparative Examples 1-5 was 1.28 mg.
[0037] Test Example 2 The materials obtained in Examples 1-4 and Comparative Examples 1-5 were mixed with 2% PVDF solution at a mass ratio of 9:1, and N-methylpyrrolidone was added as a solvent. The mixture was then stirred on a magnetic stirrer for 8 hours to obtain a slurry. This slurry was then coated onto a 1×1.5cm carbon cloth, and the coated sample was placed in a vacuum drying oven at 80℃ for 12 hours to obtain a supercapacitor electrode sheet. The loading of the supercapacitor electrode sheet in this test example was 1.6mg, and the mass of the materials obtained in Examples 1-4 and Comparative Examples 1-5 was 1.44mg.
[0038] Three-electrode system assembly: In the three-electrode system, a platinum sheet electrode is used as the counter electrode, an Hg-HgO electrode is used as the reference electrode, and the electrodes prepared in Test Example 1 and Test Example 2 are used as the working electrodes, respectively. The electrolyte is a 6 mol / L potassium hydroxide solution.
[0039] The specific capacitance variation of the supercapacitor electrodes prepared in Test Example 1 under different current densities was analyzed. Conductive carbon black was introduced into all electrodes. The test results for different materials are as follows: Figure 4 As shown. By Figure 4 It can be seen that the specific capacitance of all samples gradually decreases with increasing current density. This is because at high current densities, electrolyte ions cannot fully enter the microporous structure and can only participate in energy storage using the outer surface. However, the rate of decrease varies significantly among the samples. KCM-1.5 maintains a relatively high specific capacitance at high current densities, reaching 340 F·g. -1 It exhibits excellent rate performance. This indicates that KCM-1.5 has a more rational pore structure, in which micropores provide the main charge storage space, while mesopores and some macropores serve as ion transport channels, effectively reducing diffusion resistance. Furthermore, since the introduction of conductive carbon black has constructed a basic conductive network, the difference in rate performance reflects more the influence of the pore structure on ion transport behavior.
[0040] The specific capacitance of the supercapacitor electrodes prepared in Test Example 2 was analyzed under different current densities. No conductive carbon black was introduced into any of the electrodes. The test results for different materials are as follows: Figure 5 As shown. By Figure 5 It can be seen that the specific capacitance of all samples decreased with increasing current density, but KCM-0.75 maintained a high capacitance retention rate under high current density conditions, demonstrating good rate performance. Meanwhile, KCM-0.75 at 0.5 A·g -1 At that time, the specific capacitance reached 500 F·g -1 This indicates that in-situ grown CNTs can construct an effective intrinsic conductive network without conductive additives, ensuring good electrochemical performance of the material at low to medium current densities.
[0041] Test Example 3 The KCM-0.75 prepared in Example 1 was mixed with a 2% PVDF solution at a mass ratio of 9:1, and N-methylpyrrolidone was added as a solvent. The mixture was then stirred on a magnetic stirrer for 8 hours to obtain a slurry. The slurry was then coated onto a 1×1.5cm carbon cloth and placed in a vacuum drying oven at 80℃ for 12 hours to obtain a supercapacitor electrode sheet with a loading of 1.6mg and a KCM-0.75 mass of 1.44mg.
[0042] The KCM-1.5 prepared in Example 2 was mixed with conductive carbon black and 2% PVDF solution at a mass ratio of 8:1:1. N-methylpyrrolidone was added as a solvent, and the mixture was stirred on a magnetic stirrer for 8 hours to obtain a slurry. The slurry was then coated onto a 1×1.5cm carbon cloth and placed in a vacuum drying oven at 80℃ for 12 hours to obtain a supercapacitor electrode sheet with a loading of 1.8mg and a KCM-1.5 mass of 1.44mg.
[0043] Dual-electrode supercapacitor assembly: The supercapacitor electrode sheets prepared in Examples 1 and 2 of Test Example 3 were used as symmetrical electrodes, and the electrolyte was a 6 mol / L potassium hydroxide solution.
[0044] The cyclic stability of the dual-electrode supercapacitor was tested at 10 A·g. -1 Test results at current density are as follows Figure 6 As shown. By Figure 6 It can be seen that both samples maintained high coulombic efficiency (close to 100%) during long-term cycling, indicating good reversibility of their charge-discharge process. Regarding capacitance retention, the electrode made with KCM-0.75 as the active material (without conductive carbon black) retained 66% capacitance after 8000 cycles; while the electrode made with KCM-1.5 as the active material (with conductive carbon black) retained 87% capacitance after 8000 cycles, demonstrating excellent cycle stability. These results indicate that the carbon black-free system, relying on the intrinsic conductive network constructed by in-situ CNTs, exhibits higher specific capacitance at low rates, while the system with added carbon black, by constructing a more complete multidimensional conductive network, demonstrates superior performance in high-rate operation and cycle stability.
[0045] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon nanotube / porous carbon composite material, characterized in that, Includes the following steps: Lignite powder was mixed with K2CO3 and ground to obtain a premixed precursor. The premixed precursor was carbonized and acid-washed under an inert atmosphere to obtain a carbon nanotube / porous carbon composite material.
2. The method for preparing carbon nanotube / porous carbon composite material according to claim 1, characterized in that, The particle size of the lignite powder is ≤200 mesh.
3. The method for preparing carbon nanotube / porous carbon composite material according to claim 1, characterized in that, The mass ratio of lignite powder to K2CO3 is 1:0.75~2.
4. The method for preparing carbon nanotube / porous carbon composite material according to claim 1, characterized in that, The grinding time is 1 to 3 hours.
5. The method for preparing carbon nanotube / porous carbon composite material according to claim 1, characterized in that, The carbonization includes a first-stage carbonization and a second-stage carbonization performed sequentially; The temperature of the first-stage carbonization is 400~600℃, the holding time is 1~3h, and the heating rate to the first-stage carbonization temperature is 2~4℃ / min. The temperature for the second-stage carbonization is 800~1000℃; the holding time is 1~3h; and the heating rate to the second-stage carbonization temperature is 2~4℃ / min.
6. The method for preparing carbon nanotube / porous carbon composite material according to claim 1, characterized in that, The pickling process involves sequential washing with hydrofluoric acid, hydrochloric acid, and water; the mass fraction of the hydrofluoric acid is 15%~25%; the washing time with hydrofluoric acid is 1~3 hours; the concentration of the hydrochloric acid is 0.5~1.5 mol / L; the washing time with hydrochloric acid is 1~3 hours; and the water washing is performed until the pH of the washing solution is neutral.
7. A carbon nanotube / porous carbon composite material prepared by the method for preparing carbon nanotube / porous carbon composite material according to any one of claims 1 to 6.
8. The application of the carbon nanotube / porous carbon composite material according to claim 7 in the preparation of supercapacitor electrodes.
9. A supercapacitor electrode, characterized in that, It includes carbon nanotube / porous carbon composite materials and PVDF; the carbon nanotube / porous carbon composite material is the carbon nanotube / porous carbon composite material as described in claim 7.
10. The supercapacitor electrode according to claim 9, characterized in that, The supercapacitor electrode also includes conductive carbon black; the mass content of the conductive carbon black in the supercapacitor is 0%~10%.
